Tritium content in water bodies in regions of peaceful nuclear explosions - Repin, V. S.; Varfolomeeva, K. V.; Biblin, A. M.; Zelentsova, S. A.; Sednev, K. A.; Arkhangelskaya, G. V. (Radiacionnaâ gigiena, 2024)
Sites of peaceful nuclear explosions pose a potential radiation hazard to the territories of the Russian Federation, primarily due to the possible release of radioactivity from the explosion cavity into aquifers and onto the earth's surface. Therefore, it is essential to conduct regular monitoring of anthropogenic radionuclides in drinking water sources in settlements located near the sites of peaceful nuclear explosions. Tritium serves as an indicator of the potential release of other anthropogenic radionuclides. Monitoring its levels in water bodies in regions where peaceful nuclear explosions were perfomed, and comparing this data with that from Roshydromet across the Russian Federation, allows for an assessment of the reliability of the engineering barriers between the central explosion zone and the environment with respect to preventing radionuclide migration into aquifers. One method for evaluating the reliability of these barriers is the assessment of tritium specific activity in drinking water sources. This article presents results of the study involving 220 water samples collected from drinking water sources (wells, boreholes, springs, central water supply systems) and surface waters within 167 settlements across 17 subjects of the Russian Federation, where 50 peaceful nuclear explosions were conducted between 1965 and 1988. The samples were collected between May and September 2024 in the settlements within a 30 km radius of a peaceful nuclear explosion site. Measurements of tritium specific activity were performed using the Quantulus 1220-003 alpha-beta spectrometric radiometer. The research revealed that the specific activity of tritium in underground water sources is significantly lower (Student's test p<0,05) than in surface waters. The average specific activity levels of tritium in boreholes, rivers, and lakes were 3.0, 3.45, and 4.31 Bq/kg, respectively. The specific activity of tritium in drinking water sources within the regions of peaceful nuclear explosions was found to be at the background levels recorded by Roshydromet, ranging from 1.1 to 5 Bq/kg.